Ti3AlC2, a candidate structural material for innovative nuclear energy system: The microstructure phase transformation and defect evolution induced by energetic heavy-ion irradiation. (1st May 2020) - Deng, Tianyu; Sun, Jianrong; Tai, Pengfei; Wang, Yuyu; Zhang, Linqi; Chang, Hailong; Wang, Zhiguang; Niu, Lijuan; Sheng, Yanbin; Xue, Desheng; Huang, Qing; Zhou, Youfu; et al.
Abstract: For the structure materials applied in the innovative nuclear energy system, the strongly environment radiation source is always a big concern which will severely degrade the materials performance especially at high temperature. To explore the mechanisms of the anti-irradiation properties in Ti3 AlC2, a typical MAX phase material showing excellent irradiation damage tolerance and resistance to amorphization, we conducted a series of 1 MeV C 4+ ions irradiation experiments on them at different temperatures (RT, 300°C, 500°C and 800°C). Through Grazing Incidence X-ray Diffraction (GIXRD), Raman spectra (Raman), slow positron annihilation Doppler Broadening Spectroscopy (DBS) and high resolution Transmission Electron Microscopy (HRTEM), the anti-irradiation properties were systematically investigated. For the first time, an entire microstructure phase transformation process of Ti3 AlC2 from α to β to γ and to perfect fcc structure phase induced by irradiation at RT and it is inverse (recovery) process of phase transformation under high temperature (≥300 °C) irradiation conditions are found and confirmed. And lots of simple vacancies are induced by irradiation and the density of them gets saturated above 5 × 10 15 ions/cm 2 fluences. These processes of phase transformation and recovery and vacancy saturation phenomenon are the primary reasons for why Ti3 AlC2 has excellent irradiation damage tolerance and resistance to amorphization. In addition, the micro strain and lattice parameters are also affected by microstructure transformation and have been discussed. In a word, Ti3 AlC2 materials show good anti-irradiation properties especially at high temperature, and now it is a primary candidate as the coating of the cladding material and the spallation target beam windows material in Chinese ADS project. And studies on this kind of materials provide a promising new concept and way for designing the structural materials for innovative nuclear energy system. Graphical abstract: Image, graphical abstract